Solar home automation system (mechanical part) - Mohd Ridzwan, Ramli (2008)
This project is mainly concerned on development of solar home automation system for mechanical. The main objective in this project is to give an experience and knowledge for student to make the project and activity successfully. These projects as model to an application for a real house This project involves the process of designing the model house and assemble the parts together with electro mechanical part to complete the solar home automation system. There the many steps taken to design and fabricate the mechanical part solar home automation system. The structural three dimensional solid modeling of house system was developed by using the Solid Works engineering drawing software. In this project have 3 main process The first process is fabricate the mechanical part, the second process is fabricate the electrical part and the last one is integrated electrical part and mechanical part. The mechanical part made a model house and the electrical part made a circuit with solar panel. Lastly, two part need to integrate.